*The Sydney System in the assessment of gastritis: Inter-observer agreement - Sibel ÖZTÜRK; Ebru SERİNÖZ and Işınsu KUZU and Arzu ENSARİ and Esra ERDEN and Aydan KANSU and Buket ALTUNTAŞ and Hülya ÇETİNKAYA and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-